The farm management of shrimp farmers in Nakhon Pathom Province. - Meekam, Siwarat (Journal of Management Science Nakhon Pathom Rajabhat University, 2018)
The aims of the research were to 1) study the farm management of shrimp farmers in Nakhon Pathom Province and 2) compare the farm management of shrimp farmers, classified by individual factors. The research instrument was a questionnaire. The data was collected from 260 shrimp farmers in Nakhon Pathom Province and were analyzed for frequency, percentage, means, standard deviation, t-test and one-way analysis of variance. The research findings revealed that: 1) The farm management of shrimp farmers in Nakhon Pathom Province in general was at a high level. 2) The comparison of management, according to the individual factors, indicated that farmers who had a difference in amount of capital, farm size, business tenure or type of farm gave no difference in farm management practices. Article history : Accepted 22 March 2014 SIMILARITY INDEX = 3.12